2021
DOI: 10.1007/s00406-021-01351-y
|View full text |Cite
|
Sign up to set email alerts
|

Medium-term and peri-lockdown course of psychosocial burden during the ongoing COVID-19 pandemic: a longitudinal study on patients with pre-existing mental disorders

Abstract: While the COVID-19 pandemic continues, patients with pre-existing mental disorders are increasingly recognized as a risk group for adverse outcomes. However, data are conflicting and cover only short time spans so far. Here, we investigate the medium-term and peri-lockdown-related changes of mental health outcomes in such patients in a longitudinal study. A cohort of 159 patients comprising all major mental disorders (ICD-10 F0-F9) were interviewed twice with the Goettingen psychosocial Burden and Symptom Inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 59 publications
(105 reference statements)
4
22
0
Order By: Relevance
“…Similarly, studies in Greece and in the Netherlands observed high levels of distress but no symptoms of depression or anxiety, or changes in mental quality of life in patients with chronic disease and dialysis patients, respectively ( 14 , 41 ). Also in line with present findings is a German study investigating a cohort of patients with pre-existing mental disorders reporting an increase of psychosocial burden in patients in April/May 2020 before normalizing to pre-pandemic levels in November/December 2020 ( 42 ). At the same time, symptoms of mental disorders only changed minimally ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, studies in Greece and in the Netherlands observed high levels of distress but no symptoms of depression or anxiety, or changes in mental quality of life in patients with chronic disease and dialysis patients, respectively ( 14 , 41 ). Also in line with present findings is a German study investigating a cohort of patients with pre-existing mental disorders reporting an increase of psychosocial burden in patients in April/May 2020 before normalizing to pre-pandemic levels in November/December 2020 ( 42 ). At the same time, symptoms of mental disorders only changed minimally ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Also in line with present findings is a German study investigating a cohort of patients with pre-existing mental disorders reporting an increase of psychosocial burden in patients in April/May 2020 before normalizing to pre-pandemic levels in November/December 2020 ( 42 ). At the same time, symptoms of mental disorders only changed minimally ( 42 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nonetheless, studies identified for this review highlight a need for data pertaining to prevalence and severity of different types of DV from multiple timepoints prior to the COVID-19 outbreak and over the course of the pandemic with multiple measurements during the pandemic. Repeated assessments over the course of the pandemic are further warranted given different pandemic phases and waves, which in turn may be characterized by differential stressors ( 71 , 72 ). For instance, the COVID-19 outbreak and immediate governmental measures represented an entirely new and unknown situation for most of the global population, characterized by uncertainty and an immediate increase in stress related to employment and finances for many.…”
Section: Discussionmentioning
confidence: 99%
“…Although this initial uncertainty may by now have decreased, long-term adjustment to the pandemic and the ever-changing implications for day-to-day life may vary considerably among individuals given their specific experiences and living conditions. Thus, repeated assessments of DV over the course of the pandemic may offer the opportunity to distinguish between the pandemic's initial stress, potentially resulting in emotional turmoil, in turn increasing the risk for interpersonal aggression, vs. long-term stress, potentially resulting in emotional depletion/depression in turn also increasing the risk for interpersonal aggression ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with major mental disorders are recognized as a risk for adverse outcomes. Using the Goettingen psychosocial Burden and Symptoms Inventory (Goe-BSI), Bartels and colleagues evaluated psychosocial burden, psychiatric symptoms, and resilience at the end of the first (April/May 2020) and the second lockdown in Germany (November/December 2020) [ 1 ]. Psychosocial burden varied significantly overtime with an increase from the pre-pandemic to the initial phase, followed by a steady decrease across both lockdowns, normalizing in November/December 2020.…”
mentioning
confidence: 99%